Analysis of the Viability of Commercial Real Estate Investment in Enugu, Enugu State, Nigeria (2012-2022) - Akpaenyi, M. O.; Igwe, C. P. (International Journal of Real Estate, 2025)
Over the years, Enugu, the Capital City of Enugu State has witnessed a continuous rise in real estate investment especially in the residential aspect due to the nature of activities which was mainly administrative activities necessitated by the high presence of government offices in the State Capital and the consequent need for accommodation for government staff and officials. However, in recent times, there has been increase in business activities which has led to an increase in commercial real estate investment within the major towns in Enugu, Enugu State. This rise in commercial activities has led to the development and establishment of lock-up shops, plazas, shopping malls, financial institutions, filling stations, and many other investments in commercial real estate. This study is aimed at analyzing the viability of these commercial real estate investments in Enugu, Enugu State. The study objectives are; to identify the commercial real estate developments in Enugu from 2012 to 2022, to identify the development costs and rental values of commercial real estate projects, to determine the rate of returns from commercial real estate investments, to ascertain the risk profile inherent in commercial real estate investment in the study area and to analyze the overall performance of commercial real estate investment in Enugu, Enugu State. Research Hypotheses are formulated to test the postulation that there has been no significant increase in the rental values of commercial real estate developments in Enugu from 2012 to 2022 and, that there is no significant improvement in the viability of commercial real estate investments in the study area from 2012 to 2022. Data were retrieved from the population of the study comprising 52 Estate Surveyors and Valuers practicing in various Real Estate firms within the study area using questionnaires, interview and observation of records. The data collected were analyzed using descriptive statistics, ANOVA, SPSS and regression analysis. The findings suggest that while the commercial real estate market in the study area has experienced significant growth in terms of rental values and rate of returns, the overall viability of these investments has not improved during the period under review. The study therefore recommends further research to explore the specific drivers and constraints influencing the viability of commercial real estate investments in the study area, as well as to investigate the potential strategies and policy interventions that can be implemented to support the growth and development of this crucial sector.